ANALISIS EFISIENSI DAN EFEKTIVITAS RETRIBUSI PASAR DI KABUPATEN TIMOR TENGAH UTARA - Emilia Khristina Kiha; , Berno Benigno Mitang (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Market Service Fees are a potential source of regional revenue. This study aims todetermine the level of security of market retribution receipts such as growth ratesand their contribution to regional levies and PAD, efficiency and effectiveness levelsas well as projections of future market retribution receipts in North Central TimorRegency. The method used is descriptive quantitative analysis method, namely theanalysis of growth rate, contribution, efficiency and effectiveness as well as Trend.Overall, the observations show an average efficiency level of 87 percent, meaningthat to realize the market levy revenue of Rp. 100 required a fee of Rp. 87 and this isincluded in the category of quite efficient. This level of efficiency is quite efficientbecause the percentage increase in the cost of collecting market levies is greater.The level of effectiveness of collecting market retribution on average in NorthCentral Timor Regency during the observation shows an effective level of effectiveness because the figure obtained is 94.68%. This shows that on average thecollection of market levies has been running effectively because in each fiscal year,the figure is close to 100 percent but it is not very effective because the averageresults obtained are still below 100. the next year shows an increase that has apositive trend, meaning that the acceptance of market levies can be increased againin the future.